INFLUENCE INTELLIGENCE EMOTIONAL AND RESILIENCE PSYCHOLOGICAL TO EFFECTIVENESS LEADERSHIP IN SOCIAL ORGANIZATION LEADERS - Frederick Rudy Sentosa Rajagukguk; Indra Welly Arifin; Hastuti Handayani Harahap (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This research aims analyze influence intelligence emotional and resilience psychological to effectiveness leadership in leaders organization social services in Tebing Tinggi City . This study is important Because organization social often face limitations source power , dynamics volunteers , pressure service society , as well as need taking quick and empathetic decisions . Research​ use approach quantitative with design survey explanatory . Research sample totaling 120 leaders organization selected social​ through purposive sampling based on experience lead at least one year . Data collected use questionnaire Likert scale and analyzed through validity , reliability and assumption tests classical , correlation , and multiple linear regression . Research results show that intelligence emotional influential positive and significant to effectiveness leadership (β = 0.413; t = 5.972; p < 0.001). Resilience psychological factors also have an influence positive and significant (β = 0.352; t = 5.083; p < 0.001) . simultaneous , both variables explains 54.9% of the variation effectiveness leadership . This finding confirms that ability understand emotions , managing pressure , adapt , and remain productive in situation difficult is factor important in increase quality leadership organization social .